The dynamics of rinderpest in nomadic pastoral systems: the Somali surveillance example - Tempia, Stefano, author; Salman, M., advisor; Morley, Paul, committee member; Keefe, Thomas, committee member; DeMartini, James, committee member; Freier, Jerome, committee member (Colorado State University. Libraries, 2006)
The Somali economy is the only one in the world where over 60% of the population is dependent on nomadic pastoralism for its livelihood. Furthermore, contrary to most pastoral systems which are normally devoted to the household subsistence, the Somali system is radically oriented towards livestock trade and export. However, the complete absence of veterinary control measures, due to the collapse of the Somali Government in 1991 and the lack of appropriate techniques for investigating disease events in nomadic conditions have rendered the Somali livestock industry increasingly vulnerable and susceptible to the imposition of bans from importing countries. The most recent bans have been related to the suspicion of rinderpest (RP) and Rift Valley fever (RVF) viruses circulating among the Somali livestock population. It is currently believed that the only remaining foci of RP circulation in the world are situated in the so called Somali Eco-System which encompasses the Somali inhabited areas of Kenya and Ethiopia and the central and southern regions of Somalia. In order to delineate the extent of the remaining foci of RP in Somalia, a cross-sectional sero-survey based on a two stage cluster sampling was designed. To obtain a representative sample in the absence of a sampling frame, the random selection of the primary sampling units was attained by the use of random map coordinates. The survey was conducted in ten administrative regions of central and southern Somalia. A total of 9,216 serum samples were collected from cattle aged 1 to 3 years in 562 sampling sites. The spatial dependency of the observed sero-prevalence was tested by means of Moran's I and Local Indicator of Spatial Autocorrelation (LISA) statistics. Both tests indicated a statistically significant spatial autocorrelation of the observations, and two spatial sero-prevalence clusters were detected, suggesting the existence of two potential foci of RP maintenance in the country. Furthermore, the integration of conventional statistical techniques (i.e. logistic regression models) with spatial analysis and Geographic Information Systems (GIS) allowed the determination of the risk factors for RP maintenance and spreading as well as the estimation of the spatial risk of RP occurrence in the study area. The latter was used to develop a risk based approach for the zonation of the country according to the guidelines of the International Office of Epizootics (OIE). The study has demonstrated that the utilized methodology is able to produce reliable information from mobile livestock keeping systems. Furthermore, the study has generated important baseline data that will give a more focused direction towards the final eradication of RP in the country. At present, the proposed methodology has been recommended by the African Union - Inter-African Bureau for Animal Resources (AU-IBAR) to simultaneously investigate the status of RP in the three countries of the Somali Eco-System in order to generate relevant information that will lead the final eradication of the disease from the Horn of Africa and the world.
Keywords: virology